1998
DOI: 10.1085/jgp.112.2.113
|View full text |Cite
|
Sign up to set email alerts
|

Light Dependence of Calcium and Membrane Potential Measured in Blowfly Photoreceptors In Vivo

Abstract: Light adaptation in insect photoreceptors is caused by an increase in the cytosolic Ca2+ concentration. To better understand this process, we measured the cytosolic Ca2+ concentration in vivo as a function of adapting light intensity in the white-eyed blowfly mutant chalky. We developed a technique to measure the cytosolic Ca2+ concentration under conditions as natural as possible. The calcium indicator dyes Oregon Green 1, 2, or 5N (Molecular Probes, Inc., Eugene, OR) were iontophoretically injected via an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 50 publications
2
26
0
Order By: Relevance
“…Extrusion of Ca 2+ via the CalX Na + /Ca 2+ exchanger Within 20 ms of light stimulation, the Ca 2+ concentration in the rhabdomeral microvilli can rise from a resting Ca 2+ level of ∼160 nM, to reach peak values higher than 200 μM, before declining to a steady-state of ∼20 μM [151][152][153]. To accomplish the dynamic changes in Ca 2+ levels during the photoresponse, a rapid Ca 2+ extrusion mechanism is required to counter the TRP-dependent influx of Ca 2+ .…”
Section: The Trpc Cation Channelsmentioning
confidence: 99%
“…Extrusion of Ca 2+ via the CalX Na + /Ca 2+ exchanger Within 20 ms of light stimulation, the Ca 2+ concentration in the rhabdomeral microvilli can rise from a resting Ca 2+ level of ∼160 nM, to reach peak values higher than 200 μM, before declining to a steady-state of ∼20 μM [151][152][153]. To accomplish the dynamic changes in Ca 2+ levels during the photoresponse, a rapid Ca 2+ extrusion mechanism is required to counter the TRP-dependent influx of Ca 2+ .…”
Section: The Trpc Cation Channelsmentioning
confidence: 99%
“…Preparation and the electrophysiological methods were as described by Oberwinkler and Stavenga (1998). Briefly, the animal was immobilized and placed on the stage of a Leitz Orthoplan epifluorescence microscope (Leitz, Wetzlar, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…We have recently demonstrated that the free Ca 2ϩ concentration can be measured by recording the fluorescence emitted from Ca 2ϩ indicator dyes in single photoreceptor cells of blowflies in vivo (Oberwinkler and Stavenga, 1998). In these earlier measurements, the fluorescent signal was sampled from the entire cell.…”
Section: Recording Ca 2؉ -Induced Fluorescence From the Rhabdomere Ofmentioning
confidence: 99%
See 2 more Smart Citations